PERAN PEMERINTAH DESA TERHADAP UPAYA PEMULIHAN AKIBAT BENCANA ALAM PERSPEKTIF FIQH SIYASAH - B., Rahmawati; Larissa, Dea; Hisbullah, Hisbullah (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2022)
The natural disaster that occurred in Buakkang Village, Bungayya District, Gowa Regency in 2019 affected the damage to residents' homes and various village infrastructures. This study aims to describe the role of village governments in overcoming and restoring their territories after natural disasters. This type of research is qualitative research with a juridical and normative approach to syar'i. As the spearhead of the government, the Buakkang Village Government has carried out emergency technical measures in an effort to recover after a natural disaster, such as collecting data on the impact of damage, opening access to isolated roads through mutual aid actions and distributing assistance to affected residents. The limited recovery budget, caused the village government to classify the beneficiaries based on the level of economic ability of the residents. The responsiveness of the village government in the event of a natural disaster is the application of one of the principles of al Maqasih al Syariah, which is an effort to save the human soul (hifdz nasf).